2018
DOI: 10.17159/2413-3221/2018/v46n1a436
|View full text |Cite
|
Sign up to set email alerts
|

Poultry farming: Lessening poverty in rural areas

Abstract: The main aim of this study was to try and establish if chicken farming could be utilised for alleviation of rural unemployment and poverty. The study examined the skills and knowledge through education that would be required for successful chicken farming. The population for the study were all experts in poultry industry. This population included established and emerging chicken farmers, government officials who are involved in chicken farming projects in rural areas, veterinarians specialising in poultry, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…The findings from this study serve as the basis for chicken production improvement with regard to the management perspectives. This is because chicken production is an easy venture to reduce poverty, where everyone can get engaged regardless of his or her economic level ( Bounds and Zinyemba, 2018 ). The findings also are helpful in improving health and productivity of chickens so as to meet the demands of the growing Dodoma populations and improving the livelihoods of the chicken-keeping communities.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from this study serve as the basis for chicken production improvement with regard to the management perspectives. This is because chicken production is an easy venture to reduce poverty, where everyone can get engaged regardless of his or her economic level ( Bounds and Zinyemba, 2018 ). The findings also are helpful in improving health and productivity of chickens so as to meet the demands of the growing Dodoma populations and improving the livelihoods of the chicken-keeping communities.…”
Section: Introductionmentioning
confidence: 99%
“…Gueye (2002) asserts that poultry farming is an appropriate source of protein and can provide employment or alternative source of income for low-income households. The study of Bounds and Zinyemba (2018) found that involvement in chicken farming can alleviate rural poverty and unemployment.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The presence of private extension agents could overcome issues that emerge in the livestock business which were identified, namely the lack of skills in animal husbandry, inefficient use of livestock-raising production facilities [1], the poor knowledge of diseases, the lack of innovations in running the agribusiness [2], the lack of comprehension of the partnership contract [3], the farmers' poor entrepreneurial abilities [4], and the possibility of conflict with the community [5]. Private extension agents are one of the extension agents acknowledged by Law number 16 Year 2006 pertaining to the Extension Activity System.…”
Section: Introductionmentioning
confidence: 99%